Parental Regret Following Decision to Revise Circumcision - Bar-Yaakov, Noam; Mano, Roy; Ekstein, Margaret; Savin, Ziv; Dekalo, Snir; Ben-Chaim, Jacob; Bar-Yosef, Yuval (Frontiers in Pediatrics, 2022)
Purpose: Revision surgery for the removal of excess foreskin after circumcision is a common procedure. The decisional regret scale (DRS) is a validated questionnaire which assesses regret after medical decision making. The aim was to evaluate parental regret by means of the DRS and querying about factors associated with regret about deciding to revise their child’s circumcision. Patients and Methods: Included were all pediatric patients who underwent revision of circumcision in a single center between 2010-2016. Excluded were children who underwent revision for reasons other than excess foreskin, those who underwent additional surgical procedures during the same anesthetic session, and those who had undergone previous penile surgery other than circumcision. Response to the DRS questionnaire was by a telephone call with the patient’s parent. Regret was classified as none (a score of 0), mild (1-25), or moderate-to-strong (26-100). Surgical and baseline demographic data were obtained from the departmental database and compared between the no regret and regret groups. Results: Of the 115 revisions of circumcisions performed during the study period, 52 fulfilled the inclusion criteria, and the parents of 40 (77%) completed the DRS questionnaire. Regret was reported by 11/40 (28%: nine as mild [23%] and two as moderate-to-strong [5%]). The average age of the child in the regret group was 17 months compared to 18 months in the no regret group (p = 0.27). The median weight percentile was 43% in both groups. Surgical variables, including anesthesia type (caudal vs. no block, p = 0.65), suture type (polyglactin vs. poliglecaprone, p = 0.29), operation time (28 vs. 25 minutes, p = 0.59), and anesthesia time (55 vs. 54 minutes, p = 0.57) were not significantly different between the groups. Conclusions: Regret for deciding upon revision surgery for removal of excess foreskin post-circumcision was reported by 27.5% of parents of children who underwent revision. No clinical, surgical, or demographic characteristics predicted parental decisional regret.